Bat flies (Diptera, Streblidae and Nycteribiidae) in a Cerrado area of Goiás State, Brazil - Graciolli, Gustavo (2010)
A survey of bat flies was carried out in the Brazilian savanna (Cerrado) in the Goiás state, Brazil. We collected 227 specimens of seventeen species belonging to nine genera of Streblidae and seven specimens of four species of Basilia Miranda-Ribeiro, 1903 (Nycteribiidae). Except for Paratrichobius longicrus (Miranda-Ribeiro, 1907) (Streblidae), all species are new recorded in Goiás.